2015
DOI: 10.1080/19371918.2015.1019174
|View full text |Cite
|
Sign up to set email alerts
|

Stressors, Coping Resources, and Depressive Symptoms among Rural American Indian Older Adults

Abstract: The purpose of this study was to examine the associations of physical health stressors and coping resources with depressive symptoms among American Indian older adults age 50 years or older. The study used a convenience sample of 227 rural American Indian older adults. A hierarchical multiple regression tested three sets of predictors on depressive symptoms: (a) sociodemographics, (b) physical health stressors (functional disability and chronic medical conditions), and (c) coping resources (social support and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Kivela et al ( 168 ) investigated two waves (1984–1985 and 1989–1990) of Older Finns and noted that low religious participation increased the risk of depression in women, but not in men. These results were further expanded by Norton et al ( 167 ), Law and Sbarra ( 166 ), Sun et al ( 165 ), and Roh et al ( 170 ) who observed that older adults with higher church attendance had a reduced risk of developing depression and depressive symptoms in a short-time-interval. Hui-Chuan ( 164 ) investigated the role of NORA on the severity of depressive symptoms over a 4-year follow-up period.…”
Section: Resultsmentioning
confidence: 72%
“…Kivela et al ( 168 ) investigated two waves (1984–1985 and 1989–1990) of Older Finns and noted that low religious participation increased the risk of depression in women, but not in men. These results were further expanded by Norton et al ( 167 ), Law and Sbarra ( 166 ), Sun et al ( 165 ), and Roh et al ( 170 ) who observed that older adults with higher church attendance had a reduced risk of developing depression and depressive symptoms in a short-time-interval. Hui-Chuan ( 164 ) investigated the role of NORA on the severity of depressive symptoms over a 4-year follow-up period.…”
Section: Resultsmentioning
confidence: 72%
“…Studies have proved that exposure to life negative events, such as serious illnesses, injuries, deaths of loved ones, marital separations, break-ups of steady relationships, onset of unemployment, major financial crises, and so on, is associated with depressive disorders and anxiety [22,23]. However, there is limited epidemiologic evidence linking life negative events exposure with DS risk among Chinese older population.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have proved that exposure to life negative events, such as serious illnesses, injuries, deaths of loved ones, marital separations, break-ups of steady relationships, onset of unemployment, major nancial crises, and so on, is associated with depressive disorders and anxiety [22,23]. However, there is limited epidemiologic evidence linking life negative events exposure with DS risk among Chinese older population.…”
Section: Introductionmentioning
confidence: 99%